Complement-targeting therapeutics for ischemia-reperfusion injury in transplantation and the potential for ex vivo delivery - Delaura, Isabel F.; Gao, Qimeng; Anwar, Imran J.; Abraham, Nader; Kahan, Riley; Hartwig, Matthew G.; Barbas, Andrew S. (Frontiers in Immunology, 2022)
Organ shortages and an expanding waitlist have led to increased utilization of marginal organs. All donor organs are subject to varying degrees of IRI during the transplant process. Extended criteria organs, including those from older donors and organs donated after circulatory death are especially vulnerable to ischemia-reperfusion injury (IRI). Involvement of the complement cascade in mediating IRI has been studied extensively. Complement plays a vital role in the propagation of IRI and subsequent recruitment of the adaptive immune elements. Complement inhibition at various points of the pathway has been shown to mitigate IRI and minimize future immune-mediated injury in preclinical models. The recent introduction of ex vivo machine perfusion platforms provides an ideal window for therapeutic interventions. Here we review the role of complement in IRI by organ system and highlight potential therapeutic targets for intervention during ex vivo machine preservation of donor organs.